Spinal Anesthesia for Emergency Cesarean Section in a Parturient with Coexisting Myasthenia Gravis, Ankylosing Spondylitis, and Multiple Sclerosis: A Rare Case Report and Structured Anesthetic Approach - RTH Supraptomo; Andy Nugroho; Putri Junita Sari (HM Publisher, 2026)
Introduction: The simultaneous occurrence of myasthenia gravis, ankylosing spondylitis, and multiple sclerosis in a pregnant woman requiring emergency cesarean section is exceptionally rare and, to our knowledge, has not previously been documented. These autoimmune disorders impose overlapping neuromuscular, demyelinating, and axial-skeletal constraints that interact to make peripartum anesthetic decision-making uniquely hazardous. Case Presentation: A 34-year-old multiparous woman with a five-year history of myasthenia gravis, ankylosing spondylitis, and multiple sclerosis presented at 30 weeks' gestation with premature rupture of membranes, irregular contractions, and reduced fetal movement, alongside ptosis, diplopia, dysphagia, dysarthria, dysphonia, dyspnea, and limb weakness. She was maintained on pyridostigmine, methylprednisolone, and adalimumab with pregnancy-adjusted dosing. After multidisciplinary evaluation, emergency cesarean section was performed under single-shot spinal anesthesia using 0.5% bupivacaine 10 mg with fentanyl 25 mcg at L4-L5 via a 27-gauge Quincke needle in a single, uncomplicated pass, with a difficult-airway cart and rocuronium-sugammadex prepared as contingency. Hemodynamics remained stable apart from a transient rise in respiratory rate that resolved with oxygen. A preterm female infant weighing 1,415 g was delivered with Apgar scores of 5, 7, and 8. Mother and infant were monitored in intensive care; the mother reached the ward on postoperative day one without myasthenic crisis. Conclusion: Pregnancy with three coexisting autoimmune diseases generates synergistic, not merely additive, anesthetic risk. Carefully conducted spinal anesthesia, supported by multidisciplinary planning, disease-tailored drug selection, and a staged airway-rescue plan, achieved a safe outcome and offers a transferable framework for comparable emergencies.